Numerical and experimental study on pin-fin based cooling structure for gas turbine application - Huang, Shan (2016)
This project aims to provide an in-depth understanding on pin-fin based cooling structure for gas turbine heat transfer applications, particularly for turbine hot-path airfoil blade trailing edge cooling. Based on past researches, new cooling structures are then proposed and investigated. This thesis is comprised by four primary studies including three experimental studies and one numerical study. Transient thermochromic liquid crystal method was used to measure endwall heat transfer coefficient of the channel while lumped capacitance method was used to measure the average heat transfer coefficient of cooling structure surface in corresponding studies. The Reynolds number was evaluated and pressure drop of flow across test channel was measured by the pressure taps. Parameters, such as Nusselt number, friction factor and thermal performance index, were evaluated based on experimental results. A scaled realistic NGV (Nozzle Guide Vane) hub platform model was tested. The local heat transfer distribution of its endwall was measured by liquid crystal method. The test has been carried out at Reynolds number range from 10,000 to 40,000. Two impinging nozzle plate with nozzle diameter of 5.5mm and 11.0mm were used. General findings include low heat transfer at acute angle corner and imbalance heat transfer distribution between upstream jet impingement region and downstream pin-fin region. The heat transfer rate at pin-fin region is only 44% of that at jet impingement region. Additionally, the existence of film hole (extraction hole) upstream of pin-fin region has insignificant influence on downstream pin-fin heat transfer in this test. It is also found that the heat transfer has been enhanced by 40% when the impinging nozzle diameter was doubled. Furthermore, the buoyancy effect at inlet flow has certain impact on magnitude and distribution of heat transfer at jet impinging target surface. The new elongated pedestal structure was proposed and investigated experimentally and numerically. Four elongated pedestal test sections with D/d=5.0 and 8.0, X/d=0.8 to 1.2, S/d=1.175 to 1.5 were designed and have been tested at Reynolds number range from 6,000 to 25,000. The average heat transfer coefficient at pedestal surface has been measured by lumped capacitance method. Revealed by the results, the heat transfer coefficient of pedestal surface could be at most 70% higher than that of endwall. Meanwhile, the pedestal surface could account for 50% of overall heat transfer at specific cases. The elongated pedestal structure enhanced the endwall heat transfer up to 9 times compare to reference data. Moreover, the elongated pedestal structure achieved similar heat transfer level comparing with perforated blockage structure but obtained 3 times higher heat transfer enhancement comparing to circular pin-fin structure. Generally, the tightly spaced structure obtained higher overall heat transfer than that of widely spaced structure which is same as circular pin-fin array. Via the numerical study, the flow behavior of elongated pedestal array is more like the turning flow inside the bending duct instead of flow around pin-fin structure. An extra structure, known as split elongated pedestal, has been studied numerically. However, the split elongated pedestal did not show significant improvement as expected in heat transfer enhancement as well as overall thermal performance. Currently split opening did not lead to significant flow interaction between two split parts. But it is recommended to further investigate this structure with much smaller split opening. Furthermore, three test sections with multiply cooling structure implemented were studied at Reynolds number range from 9,000 to 30,000. In addition, the test sections were modified in order to generate non-uniform inlet flow. One key finding is that the non-uniform inlet flow generated in this study leads to 25%-30% reduction in endwall heat transfer. Compare to circular pin-fin structure, cooling structure with high duct cross-section area block ratio, such as elongated pedestal and perforated blockage, provided more desired heat transfer distribution and higher heat transfer rate. Benefited from turbulence promotion by upstream pin-fin array, the heat transfer of downstream cooling configurations have been improved by 51%, 42% and 73% for pin-fin array, elongated pedestal array and perforated blockage array, respectively.